2020
DOI: 10.14716/ijtech.v11i1.1332
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of a Patient-Handling Technology Prototype

Abstract: Nursing jobs have generally been associated with poor posture and heavy exertion, particularly during patient-handling activities. Such working conditions are known to increase the risk of musculoskeletal disorders, and the use of patient-handling aids has been proposed to alleviate the problem. This study was conducted with the purpose of evaluating a patient-handling technology (PHT) prototype that was developed by the researchers for use in Indonesia. An experiment was conducted involving 12 nurse participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…All nine studies that evaluated motorized assistive device were designed as pre-post research designs. They included the use of mechanically powered lift systems such as floor lifts (Iridiastadi et al, 2020), ceiling lifts (Miller et al, 2006), portable full-body or stand-up lifts (Li et al, 2004), powered beds with air-assisted device and the turn assist features (Budarick et al, 2020; Wiggermann, 2016, 2017; Zhou & Wiggermann, 2021), and tilting operating room table (Al-Qaisi et al, 2020) as interventions. Based on the results, most studies reported a significant improvement in the primary outcomes of WMSDs ( SMD = −3.32, 95% CI = [−4.53, −2.12]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All nine studies that evaluated motorized assistive device were designed as pre-post research designs. They included the use of mechanically powered lift systems such as floor lifts (Iridiastadi et al, 2020), ceiling lifts (Miller et al, 2006), portable full-body or stand-up lifts (Li et al, 2004), powered beds with air-assisted device and the turn assist features (Budarick et al, 2020; Wiggermann, 2016, 2017; Zhou & Wiggermann, 2021), and tilting operating room table (Al-Qaisi et al, 2020) as interventions. Based on the results, most studies reported a significant improvement in the primary outcomes of WMSDs ( SMD = −3.32, 95% CI = [−4.53, −2.12]).…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with previous studies, significant intervention effects were observed for assistive devices, of which motorized assistive devices were found to be the most effective intervention in reducing the risk of WMSDs (Abdul Halim et al, 2023; Aslam et al, 2015). The use of technologically advanced assistive devices like a motorized portable lift, air-assisted devices, and powered beds imposed less awkward postures, physical demand, pain intensity, and discomfort than a nonmotorized assistive device (Budarick et al, 2020; Hwang et al, 2019; Iridiastadi et al, 2020; Miller et al, 2006; Wiggermann, 2017; Zhuang et al, 2000). Nevertheless, our analysis found that nonmotorized assistive devices were also effective in reducing WMSD risks.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that in future, the parameters affecting implant stability can be evaluated together with other dynamic properties such as stress, strain, and displacement of the implant during dynamic process and loading, such as daily mastication. Hence, the implant stability is not only correlated with the static parameters, but also can be connected with those dynamic properties for better understanding and monitoring of the implant biomechanically (Iridiastadi et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The use of air-assisted transfer devices can reduce the burden when repositioning patients with all types of body weight, but this tool is rarely owned by hospitals (Wiggermann et al, 2021). Other types of tools, such as prototype moving tools, lift velocity, and motorized patient transfer devices (MPTD), have higher effectiveness and are proven to reduce musculoskeletal disorders; however, the weakness of these tools is related to the speed of the tool's response, which needs further evaluation and is still rarely used in hospitals (Law et al, 2022;Iridiastadi, Vani and Yamin, 2020;Iwakiri, Sotoyama and Takahashi, 2021).…”
Section: Discussionmentioning
confidence: 99%